Hubungan antara Penyobekan Daun Secara Mekanik terhadap Serangan Penggulung Daun Pisang - Isnadian Yandhi Pratiwi; Supriyadi Supriyadi; Sholahuddin Sholahuddin (Universitas Sebelas Maret, 2020)
Mechanical control as an effort to reduce Erionata thrax attacks needs to develop of them was torning the leaves. The objective of this research was to determine the effect of leaf torning on the intensity of the damage and determine the level of E. thrax attack damage in various cultivars. This research was conducted in Semarang, Central Java from September-December 2018. This research used a field experiment method with four treatments of tearing distance of 0 cm, 20 cm, 30 cm, and 40 cm in four banana cultivars, namely Mas Kirana, Ambon, Kepok, and Raja Bulu. The result showed that leaf damage was related to torning distance, but not to the cultivars. The value of regression between torning distance and leaf damage was very low. The torning distance of 40 cm had the highest leaf damage, number of larvae populations, and number of leaf rolls. The torning distance of 20 cm reduced the leaf damage, the number of larvae populations and the number of rolls. The lowest leaf damage is in Mas Kirana cultivar and the highest leaf damage is in Raja Bulu cultivars. Raja Bulu cultivar had the highest attack intensity.